A theoretical model for estimation of work function reduction for MXenes with hydroxyl termination - Strikha, M. V.; Antoniuk, D. V. (Physics and Chemistry of Solid State, 2023)
This article presents a simple model that explains significant reduction of work function in MXenes Тіn+1Сn with hydroxyl termination and demonstrates matching results to ones in the existing literature, obtained via complex computing based on the first principles. This model can be applied for results evaluation of the hydroxyfunctionalization of various MXene types, due to prospects of the creation of novice emission electronics devices.